Recent Progress in Chemical and Chemoenzymatic Synthesis of Carbohydrates - Muthana, Saddam (2009)
The important roles that carbohydrates play in biological processes and their potential application in diagnosis, therapeutics, and vaccine development have made them attractive synthetic targets. Despite ongoing challenges, tremendous progresses have been made in recent years for the synthesis of carbohydrates. The chemical glycosylation methods have become more sophisticated and the synthesis of oligosaccharides has become more predictable. Simplified one-pot glycosylation strategy and automated synthesis are increasingly used to obtain biologically important glycans. On the other hand, chemoenzymatic synthesis continues to be a powerful alternative for obtaining complex carbohydrates. This review highlights recent progress in chemical and chemoenzymatic synthesis of carbohydrates with a particular focus on the methods developed for the synthesis of oligosaccharides, polysaccharides, glycolipids, and glycosylated natural products.